Through‐Process Modeling of Materials Fabrication: Philosophy, Current State, and Future Directions - Gottstein, Günter (Microstructural Design of Advanced Engineering Materials, 2013)
Through‐process modeling is an indispensible basis of integrated computational materials engineering, to identify the “materials genome.” In this chapter, the through‐process modeling concept of solid‐state processing of metallic materials is introduced, reviewed, and critically assessed. The concept is based on the fundamental theorem of materials science that the microstructure of a material constitutes the state parameter of material properties. The change of microstructure during processing requires a holistic consideration of microstructural change along the processing chain. Respective multiscale modeling approaches are introduced and eventually utilized for a through‐process modeling exercise of aluminum sheet fabrication. Deficiencies and needs are outlined to guide future developments.